Meta-Barcoding accelerates species discovery and unravel great biodiversity of benthic invertebrates in marine sediments in Campos basin, Brazil - Schettini, Milena Marcela D P; Cardenas, Raony G C C L; Detoni, Marcella A A; Rebelo, Mauro F (PeerJ Preprints, 2016)
Biodiversity is currently assessed for environmental characterizations and monitoring through a laborious and time-consuming process of morphological taxonomy. We used rRNA 18S, rRNA 28S and COI, together with NGS and Bioinformatics to identify benthic invertebrate organisms from sediment samples collected in five stations in the Campos Basin in southeast Brazil, an important oil extraction area and one of the best-studied marine biota in Brazil. A total of 3.3 million sequences were clustered in Operational Taxonomic Units and more than 1.6 million sequences (about 50% of all reads) were assigned to 957 prokaryotes and 577 eukaryotes. BLAST identified 23 phyla, 60 classes, 62 orders, 70 families, 67 genus and 46 species of eukaryotes. By meta-barcoding we identified phyla that are traditionally found in samples of marine benthos, such as Annelida, Arthropoda, Mollusca and Chordata, as well as rare phyla like Entoprocta and Gastrotricha. Taxa identified with meta-barcoding were compared to morphology data from previous studies in the area (REVIZEE, Habitats Project) and geo-validated with the database Global Biodiversity Information Facility. For several taxa, this is the first evidence of occurrence in Campos the area and the number of OTU identified suggests an enormous unveiled benthic biodiversity in Campos Basin. Our study supports the application of Meta-Barcoding for environmental characterization and monitoring programs, reducing from years to few months the time currently required for species identification and biodiversity determination.
Keywords: rRNA 18S; rRNA 28S; COI; Metagenomics